2012
DOI: 10.1152/ajpendo.00067.2012
|View full text |Cite
|
Sign up to set email alerts
|

Insulin fails to enhance mTOR phosphorylation, mitochondrial protein synthesis, and ATP production in human skeletal muscle without amino acid replacement

Abstract: Barazzoni R, Short KR, Asmann Y, Coenen-Schimke JM, Robinson MM, Nair KS. Insulin fails to enhance mTOR phosphorylation, mitochondrial protein synthesis, and ATP production in human skeletal muscle without amino acid replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 28 publications
1
39
1
1
Order By: Relevance
“…These results are also supported by other studies [17, 20, Louard et al(a) 1992 [19] Fryburg et al 1995 [26] Timmerman et al (1b) 28-31, 34, 44]. In all healthy human studies where AA availability has been reduced, MPS has been reduced or remained unchanged [18,19,37,45,46], even in the presence of supraphysiological concentrations of insulin [18]. The meta-analysis of the 25 studies showed that insulin exerts its regulation of lean muscle mass principally via an anticatabolic effect in reducing MPB.…”
Section: Discussionsupporting
confidence: 81%
“…These results are also supported by other studies [17, 20, Louard et al(a) 1992 [19] Fryburg et al 1995 [26] Timmerman et al (1b) 28-31, 34, 44]. In all healthy human studies where AA availability has been reduced, MPS has been reduced or remained unchanged [18,19,37,45,46], even in the presence of supraphysiological concentrations of insulin [18]. The meta-analysis of the 25 studies showed that insulin exerts its regulation of lean muscle mass principally via an anticatabolic effect in reducing MPB.…”
Section: Discussionsupporting
confidence: 81%
“…Potential explanations include that degradation of damaged ribosomal proteins may have preserved the protein quality and that there is no evidence showing that protein synthesis is directly proportional to the ribosomal protein content. Previous work has shown that the availability of amino acids, which are released following protein degradation, is critical to maintain protein synthesis (2,36). However, as we have reported previously, insulin deprivation increases net protein degradation (35), and longer periods of insulin deprivation would significantly reduce the content of muscle proteins whose degradation continues to exceed synthesis.…”
Section: Discussionmentioning
confidence: 47%
“…Phosphorylation of mTOR at S2448 tended to increase following leucine treatment and mechanical stretch and decreased following insulin treatment; however, these differences were not significant. In contrast, the phosphorylation of Akt at S473 was markedly increased by the addition of insulin in both control and stretched [46] reported that sustained insulin infusion without amino acid replacement causes sustained stimulation of Akt phosphorylation, without downstream stimulatory effects on mTOR phosphorylation. These results suggest that Akt-induced upregulation of mTOR phosphorylation at S2448 may not be essential for p70S6K activation by mechanical stretch and nutrient supplementation in C2C12 cells.…”
Section: Discussionmentioning
confidence: 90%